Medication-Related Osteonecrosis of the Jaw Spontaneously Occurred in a Patient with Chronic Myelogenous Leukemia Only by Imatinib: A Report of a Rare Case - Makiko Okubo-Sato; Kenji Yamagata; Satoshi Fukuzawa; Kazuhiro Terada; Fumihiko Uchida; Naomi Ishibashi-Kanno; Hiroki Bukawa (Case Reports in Dentistry)
The prevalence of medication-related osteonecrosis of the jaw (MRONJ) associated with molecular-targeted therapies such as bevacizumab and sunitinib has been constantly increasing in recent years. MRONJ frequently occurs after invasive dental procedures such as tooth extraction in patients currently or with a previous history of receiving antiresorptive agents including bisphosphonates and/or denosumab. Here, we report a rare case of spontaneously occurring MRONJ of the mandible in a 52-year-old Japanese woman with chronic myelogenous leukemia (CML) who was administered imatinib for 9 years. She had never been treated with antiresorptive agents, and her MRONJ developed spontaneously. Although there have been few reports of MRONJ related to imatinib, our case reported here indicates that imatinib may be capable of causing spontaneous MRONJ.